English Vocabulary Size of Second-Semester Students at Universitas Indonesia Timur: A Diagnostic Study Based on Paul Nation's Vocabulary Size Framework - Suci Ayu Kurniah P; Rusliana; Novalia Tanasy; Joko Purwanto; Aisyah (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2026)
This study investigated the English vocabulary size of 34 second-semester students at Universitas Indonesia Timur as an indicator of their academic lexical readiness. A descriptive quantitative design was employed, and data were collected through an online vocabulary size test administered via VocabularySize.com. The scores were analyzed using descriptive statistics and grouped into 1,000-word bands. The findings showed that students’ vocabulary-size scores ranged from 300 to 6,000, with a mean of 3,600.00 and a standard deviation of 1,663.330. The largest proportion of students was in the 3,000–3,999 band, while 61.8% scored below 4,000, 38.2% reached 4,000 or above, and only 29.4% reached 5,000 or above. Interpreted through Paul Nation’s lexical-threshold framework, the average score indicates that the students have basic to lower-intermediate receptive vocabulary knowledge but remain below the estimated threshold for independent academic reading and adequate spoken-text comprehension. These results suggest the need for diagnostic, level-based vocabulary instruction that strengthens high-frequency, mid-frequency, academic, and discipline-specific vocabulary. The study contributes local empirical evidence from an Eastern Indonesian higher-education context and offers a practical basis for English for Academic Purposes instruction.